2018
DOI: 10.3390/cryst8070263
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Carbonate Polymorphs Growing in the Presence of Sericin: A New Composite Mimicking the Hierarchic Structure of Nacre

Abstract: Bioinspired self-assembled composite materials are appealing both for their industrial applications and importance in natural sciences, and represent a stimulating topic in the area of materials science, biology, and medicine. The function of the organic matrix has been studied from the biological, chemical, crystallographic, and engineering point of view. Little attention has been paid to the effect of one of the two main components of the organic matrix, the sericin fraction, on the growth morphology of calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…as the 2D-sericin ordered layers work in between aragonite and calcite crystals in assembling the mollusk shells [36]. Figure 2, the elongated HAp platelets do nucleate successively, giving rise to complex arrangements, welded either on the 101 or {001} faces (or both, as drawn in Figure SI4), respectively represented in (d,e).…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…as the 2D-sericin ordered layers work in between aragonite and calcite crystals in assembling the mollusk shells [36]. Figure 2, the elongated HAp platelets do nucleate successively, giving rise to complex arrangements, welded either on the 101 or {001} faces (or both, as drawn in Figure SI4), respectively represented in (d,e).…”
mentioning
confidence: 92%
“…The few Ca-citrate layers favouring the formation of the flattened and fence-like HAp morphology assume the function of the "mortar" cementing the apatitic crystal, in the same way as the 2D-sericin ordered layers work in between aragonite and calcite crystals in assembling the mollusk shells [36]. as the 2D-sericin ordered layers work in between aragonite and calcite crystals in assembling the mollusk shells [36].…”
mentioning
confidence: 99%
“…The sericin wraps the fi broin completely or partially and binds various layers of silk into a natural nonwoven compound material to assist silkworms in constructing the space for the growth and development of pupae, i.e., cocoons [1][2][3][4][5][6][7]. Studie s have shown that the sericin outside the fi broin contains a mixture of pigment, grease, waxiness, and inorganic salts and plays a good role in protecting the fi broin to a certain extent [8,9]. The cocoon can be divided into the cocoon coat, cocoon layer, and cocoon lining from outside to inside, and there is a signifi cant difference in the content of sericin [10], so that the content of sericin in cocoon coat is close to 1.5 and 2 times that in the cocoon layer and cocoon lining respectively [8,9,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The formation of crystalline polymorphs with desired properties is controlled by different and occasionally synergic processes, such as the regulation of respective ion concentrations, the formation of initial amorphous and other metastable precursor phases, and the presence of specific biomolecular additives [ 11 ]. Extensive research has shown that living organisms require biomolecular additives such as proteins and polysaccharides with carboxyl, phosphate and sulfate groups to control the hierarchical structure and the mechanical properties of calcium carbonate [ 10 , 12 ]. These biomolecules can act as templates and control the polymorphs, orientation and morphology of calcium carbonate.…”
Section: Introductionmentioning
confidence: 99%